Analisis Optimalisasi Sistem GMDSS untuk Mendukung Keselamatan Pelayaran di Stasiun Radio Pantai - Dara Ngahu, Besaliel; Jayati, Ari Endang; Erlinasari (Forum Pendidikan Tinggi Teknik Elektro Indonesia Pusat, 2025)
This study analyzes the optimization of frequency coverage in the Global Maritime Distress and Safety System (GMDSS) implemented at the Coastal Radio Station (SROP) of PT Panorama Graha Teknologi. As Indonesia is a maritime country with high dependence on sea transportation, reliable navigation and communication systems are crucial to ensure safety. However, operationalization of GMDSS still faces limitations such as partial system integration, inadequate equipment, and lack of operator skills. The research method included direct observation and system testing at PT Panorama Graha Teknologi. Results show that the use of repeater devices significantly improves VHF frequency coverage, reduces blank spots, and enhances communication clarity between ships and coastal radio stations. The study concludes that repeater implementation provides an effective solution for optimizing GMDSS coverage, thus supporting maritime safety and communication reliability.